Factor Analysis of Militant Attitudes with Prophetic Intellectual Principles in Muhammadiyah Organizations in Higher Education - Lidya Mustika Putri; Rihab Wit Daryono (Universitas of Muhammadiyah Makassar, 2024)
Understanding the factors that influence militancy among Muhammadiyah students is important because it can provide in-depth insight into the social and political dynamics within the organization. This research aims to analyse the factors that shape militancy attitudes with prophetic intellectual principles in the student organizations of the Muhammadiyah Jamaluddin Al-Afghani Commissariat IAIN Ponorogo. The purposive sampling method was used to determine research participants from 44 student communities at the Muhammadiyah Jamaluddin Al-Afghani IAIN Ponorogo Commissariat. Data collection was carried out using a questionnaire consisting of a 4-point Likert scale. PLS-SEM analysis was used to analyse the data and test the model context. The analysis results show that interest, humanity, independence, and religiosity have a positive and significant influence on intellectual principles in the student organizations. However, talent has a negative and insignificant influence, while loyalty has a positive but insignificant influence on intellectual principles. These findings highlight the importance of building independence, interest, humanity, and religiosity in facilitating the formation of intellectual attitudes in organizational members. The practical implication is the need for a holistic approach in cadre development, which focuses on technical organizational aspects and psychological and spiritual aspects such as independence, interest, concern, humanity, and religiosity. This research supports efforts to design cadre programs that strengthen members' independence, interests, humanity, and religiosity and integrate these principles as an effective strategy for forming rational intellectual attitudes and militancy.